2004
DOI: 10.1016/j.fluiddyn.2004.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional buoyant convection in a rectangular cavity with differentially heated walls in a strong magnetic field

Abstract: Three-dimensional buoyant convection in a rectangular cavity with a horizontal temperature gradient in a strong, uniform magnetic ÿeld is considered. The walls of the cavity are electrically insulating. An asymptotic solution to the problem in the inertialess approximation is obtained for high values of the Hartmann number, Ha. In the presence of either the vertical or the horizontal longitudinal ÿelds, the three-dimensional ow is characterised by high-velocity jets at the walls of the cavity parallel to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…result in significant three-dimensional effects, especially if the so-called parallel layers are involved. Examples of such flows include buoyant convection in a cavity in a vertical and transverse magnetic fields, 4,8,[13][14][15][16][17] flows with Hunt's jets, [18][19][20][21] flows in bends, 22,23 circular ducts in a nonuniform magnetic field, 24,25 etc. In some situations, usually involving a pair of parallel electrically insulating walls transverse to the sufficiently strong magnetic field, the flow becomes quasi-twodimensional ͑Q2D͒.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…result in significant three-dimensional effects, especially if the so-called parallel layers are involved. Examples of such flows include buoyant convection in a cavity in a vertical and transverse magnetic fields, 4,8,[13][14][15][16][17] flows with Hunt's jets, [18][19][20][21] flows in bends, 22,23 circular ducts in a nonuniform magnetic field, 24,25 etc. In some situations, usually involving a pair of parallel electrically insulating walls transverse to the sufficiently strong magnetic field, the flow becomes quasi-twodimensional ͑Q2D͒.…”
Section: Introductionmentioning
confidence: 99%
“…26 Models of Q2D flows have been developed for the flow between parallel planes in a uniform magnetic field, 27,28 a nonuniform magnetic field, 29,30 or buoyant convection in a uniform field. 7,8,11,12 More elaborate Q2D models have been developed by Pothérat et al, 31,32 which take into account small but finite Ekman pumping in the Hartmann layers.…”
Section: Introductionmentioning
confidence: 99%
“…They found that a vertical magnetic field strongly reduces both the integral and local heat transfer coefficients. Aleksandrova and Molokov [1] studied buoyancy-induced convection in a rectangular cavity with a horizontal temperature gradient in a strong uniform magnetic field. They found that the flow pattern differs significantly for different magnetic field orientations.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports on this can be found in literature [1][2][3][4][5]. The process of manufacturing materials in industrial problems involve an electrically conducting fluid subjected to a magnetic field [6][7][8][9]. The fluid properties like viscosity and thermal conductivity are varying with temperature in nature.…”
Section: Introductionmentioning
confidence: 99%